Kontribusi Kompetensi Dan Supervisi Keperawatan Terhadap Efektivitas Kinerja Perawat Pada Rumah Sakit Di Provinsi Maluku Utara - Adref, Ferry; Mattalatta; Hasmin; Ansar; Kurniawaty (Khazanah Journal: Economics, Muamalah & Entrepreneurship, 2025)
This study aims to examine the effect of nursing competence and supervision on nurse performance at a Hospital in North Maluku Province. The study population was part of the nursing staff at a Hospital in North Maluku Province. The sampling technique in this study was purposive sampling, so the number of samples interested was 145 people. The analysis method used in this study is correlation analysis and t-test. This study found the equation Y = 0.137 + 0.800X1 + 0.227X2. Competence has a positive and significant effect on nurse performance where t count is 10.893 > t table 1.65 with a significance of 0.000 and nursing supervision has a positive and significant effect on nurse performance where t count> t table or 3.817> 1.65 with a significance of 0.000